2014
DOI: 10.1186/s13054-014-0687-6
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastometry and organ failure in trauma patients: a prospective cohort study

Abstract: IntroductionData on the incidence of a hypercoagulable state in trauma, as measured by thromboelastometry (ROTEM), is limited and the prognostic value of hypercoagulability after trauma on outcome is unclear. We aimed to determine the incidence of hypercoagulability after trauma, and to assess whether early hypercoagulability has prognostic value on the occurrence of multiple organ failure (MOF) and mortality.MethodsThis was a prospective observational cohort study in trauma patients who met the highest trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Comparison with a large sample of non-trauma volunteers without an activator enabled identification of this change in coagulation following injury. A large multicenter study using tissue factor to activate the viscoelastic assays showed that 10% of trauma patients had a hypercoaguable state within 24 h of injury [33]. The use of tissue factor may have masked endogenous circulating factors that promote clot formation following trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with a large sample of non-trauma volunteers without an activator enabled identification of this change in coagulation following injury. A large multicenter study using tissue factor to activate the viscoelastic assays showed that 10% of trauma patients had a hypercoaguable state within 24 h of injury [33]. The use of tissue factor may have masked endogenous circulating factors that promote clot formation following trauma.…”
Section: Discussionmentioning
confidence: 99%
“…(C) α‐angle measured in degrees (dotted lines are reference values*: 61–83 degrees). (D) G‐value measured in dynes/cm2 (dotted lines are reference values*: 5–11.7 dynes/cm2) . * = Based on human reference values.…”
Section: Resultsmentioning
confidence: 99%
“…Balanced resuscitation with blood products in ratios similar to whole blood is the mainstay to treat trauma‐induced coagulopathy and prevent exsanguination. However, transfusion is associated with adverse effects, including multiple organ failure (MOF) and nosocomial infection . The mechanisms by which transfusion exerts these effects probably include modulation of the host coagulation and immune response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Certain components of "the lethal triad" such as acidosis with blood рН below 7.2 [43], hypothermia below 35°С [44,53,54] or hypocoagulation [55][56][57][58] are also independent risk factors for unfavorable outcome. Hypothermia is associated with such polytrauma death predictors as blood loss, acidosis and coagulopathy [59].…”
Section: Evaluating the Severity Of Functional Disordersmentioning
confidence: 99%